Effect of protein A-immunoadsorption therapy on serum cytokines in AAV patients - Li, Xiejia; Li, Zheng; Deng, Hongmei; Sun, Cuifang; Liu, Hong; Yuan, Fang (Penerbit Universiti Kebangsaan Malaysia, 2022)
Protein A-immunoadsorption (IA) is an extracorporeal apheresis technique used in patients with autoimmune diseases which aims to remove pathogenic autoantibodies. Apart from the adsorption of immunoglobulins (IgG), IA may influence cellular and humoral immunity. The aim of this study was to observe the effect of protein A-IA on cytokine networks in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) patients. A total of 12 newly diagnosed AAV patients received IA therapy on days 1, 3, and 5. Serum levels of inflammatory cytokines were measured before and after treatment including members of the interleukin family, PDGF-BB, TNF-α and IFN-γ. IL-1β, IL-9, IL-17A, PDGF-BB, IFN-γ, and TNF-α were elevated in AAV patients compared to healthy individuals. There were no changes in the levels of any cytokines after the first IA session but after 3 sessions, IL-9, PDGF-BB, and TNF-α dramatically decreased. Moreover, reductions in IL-9 levels were positively correlated with the changes of myeloperoxidase-ANCA (MPO-ANCA). Our observations suggest that protein A-IA therapy does not directly adsorb cytokines, but removes autoantibodies (MPO-ANCA) which indirectly leads to changes in cytokine networks linked to cellular or humoral immunity.